Surgical treatment for intravenous-cardiac leiomyomatosis. (3rd March 2018) - Liu, Jianzhou; Liang, Mei; Ma, Guotao; Liu, Xingrong; Cheng, Ninghai; Cao, Dongyan; Yu, Chunhua; Du, Shunda; Miao, Qi; Zhang, Chaoji
Abstract: OBJECTIVES: There are few published studies on the rare disorder of intravenous-cardiac leiomyomatosis (IVCL). This study aimed to propose an individualized strategy for surgical treatment of IVCL. METHODS: In this retrospective study, we reviewed 50 patients who had undergone IVCL removal from November 2002 to October 2017 in our hospital. IVCL was classified as Type A–E according to the extent and size, with Type E being the most severe. Clinical manifestations, surgical features and follow-up data were analysed. RESULTS: Of the 50 patients in this series, 8 had Type A IVCL, 8 Type B, 29 Type C, 2 Type D and 3 Type E IVCL. One-stage removal of IVCL was performed via laparotomy without cardiopulmonary bypass (CPB) in the 8 patients with Type A, 1-stage tumour resection via sternolaparotomy under deep hypothermic arrest in 7 of the 8 patients with Type B and IVCL removal via sternolaparotomy under CPB, with 27 also under deep hypothermic arrest, in all 29 patients with Type C. Sixteen of the patients with Type C IVCL underwent staged procedures, 13 a 1-stage procedure and 21 required hepatic mobilization. All patients with Type C or E cases underwent 1-stage tumour removal via sternolaparotomy under deep hypothermic arrest. All 50 patients survived surgery. IVCL was confirmed postoperatively by histology. Ten patients had residual tumours; 9 of which did not progress. No deaths occurred during 47.8 ± 38.4 (range 1–177) months of follow-up. CONCLUSIONS: The only known curative treatment for IVCL is surgery. Herein, we present an individualized strategy for selecting surgical treatment.